Using Cartoon Film to Enrich the Vocabulary - Fitri Radhiyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study tried to find out whether the use of English cartoon Films was able to enrich the vocabulary of the students. The method used was pre-experimental which involved one group pretest and posttest design. The population was the third-year students of SLTPN 1 BULUKUMPA, and the sample consisted of 30 students taken randomly from six classes. The instrument used was a vocabulary test. To analyze the data, a t-test was used. The mean score of the pretest is 4.94 and the post-test is 7.30. The result of the t-test analysis shows that the value of the t-test (13.07) is greater than the value of the t-table (2.045) at the level of significance .0S with a degree of freedom 29. It means that there is a significant difference between the result of the students’ pretest and the posttest. It is concluded that the use of cartoon film is an effective medium to improve the vocabulary command of the students of SLTPN 1 BULUKUMPA.